The impact of Work Stress on Work Family Conflict: A Mediated Model Using Job Satisfaction In The Hotel Industry - Syamsul Hadi; Didik Subiyanto; Aprielle Ego Pasha; Enggar Kartika C. (SMARTINDO, 2023)
Purpose – The Purpose of this study is to investigated the impact of work stress on work family conflict: a mediated model using job satisfaction in the hotel industry Design/methodology/approach – The sampling technique used in this study is a non-probability sampling technique, which is known as purposive sampling. The amount of samples used in this study are 48 respondents who work as employees of Hotel Industry. The research method that used in this study are multiple linear regression analysis and sobel test. Findings – The results of this study indicate that work family conflict has a negative and significant effect to job satisfaction, work family conflict has no positive and significant effect on work stress, and work stress has a negative and significant effect on job satisfaction, while work stress is able to mediate the effect of work family conflict on job satisfaction.